Diversity of cultivable bacteria by strategic enrichment isolated from farmed edible red seaweed, Gracilaria sp. - Abdullah, Najatul Suad; Mohamad, Mohd Azrul Naim; Mohammad Noor, Normawaty; Zainal Abidin, Zaima Azira (Zibeline International Publishing, 2020)
Research on bacteria associated with various red seaweed species are emerging due to the interest to understand bacteria-seaweed interaction and functional roles of bacteria in a seaweed environment. Edible red seaweed, Gracilaria sp. is farmed primarily in China, followed by Indonesia and Malaysia but little is known on its associated bacteria and potential functions. This study aimed to isolate and identify cultivable bacteria from extracts of seaweed samples collected from a seaweed cultivation farm in Kedah, Malaysia. The results are hoped to provide insights into beneficial bacteria that exist in the farmed seaweed environment. Through cultivation on strategic enrichment media, 18 isolates OTUs were identified from bacterial phyla Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria. These phyla are ubiquitous in seawater and some isolates were homologous to bacteria in marine host cluster. Further investigation on these isolates is hoped to reveal how the isolated bacteria can be beneficial in a seaweed environment or for other biodiscoveries